Heutagogy as an alternative in teacher education: conceptions of lecturers and pre-service teachers of school of education and life-long learning, SDD-UBIDS - Mwinkaar, Linus; Lonibe, Jane-Frances Yirdong (Frontiers in Education, 2024)
The needs of today's higher education have changed and higher education doesn't need a one-way communication from teacher to student but rather learn to appreciate the new role of the teacher as a facilitator with mutual responsibilities towards the creation of knowledge. Heutagogy, which emphasizes learner autonomy and the creation of self-determined learners, has garnered attention as a potential solution to address the evolving needs of teacher preparation. However, empirical research on the beliefs and attitudes of Heutagogy within the teacher education context remains limited. This study aimed to fill this gap by exploring the beliefs and attitudes of lecturers and pre-service teachers of the School of Education and Life-Long Learning (SoELL) at SDD-UBIDS.Methods: Convergent mixed method design with both quantitative and qualitative data analysis, the study collected both quantitative and qualitative data on 513 Pre-service teachers and 30 Lecturers from SoELL, SDD-UBIDS using a four-point Likert scale questionnaire and interview.The findings revealed diverse perspectives among Lecturers and Pre-service Teachers regarding Heutagogy, with varying levels of understanding, acceptance, and readiness for implementation. Lecturers expressed enthusiasm for Heutagogy's potential to foster learner autonomy and critical thinking skills, while pre-service teachers demonstrated varying levels of readiness and comfort with self-directed learning approaches.Discussion: Lecturers and Pre-service teachers expressed willingness to embrace a selfdetermined approach in which the learner reflects on what is learned and how it is learned and where the Lecturers teach the learners how to learn by themselves. The cognitive conflict and the inadequacy of pre-service teachers' preparedness will necessitate a shift in their attitudes towards developing autonomy skills to effectively navigate the challenges of the 21st-century knowledge economy.